PENGEMBANGAN MEDIA SMART ROULLETE UNTUK MENGEMBANGKAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN - Rohyana Fitriani; Novitasari Utami; Suhirman Suhirman (Jurnal Golden Age, 2021)
The purpose of this study was to develop a smart roulette learning media to improve the social and emotional aspects of children aged 5-6 years. The development model used is Borg and Gall which consists of six stages. The products developed are validated by a team of experts. The small scale subjects were 5 children and the large scale subjects were 15 children. The instrument used to collect data is an observation sheet. The results showed that the results of the media expert's validation obtained a score of 42 with an average value of 5.25 in the "very good" category, the results of the material expert validation obtained a score of 29 with an average value of 4.14 in the "good" category. The results of the observations obtained that the percentage of success for the pretest was 43% (MB) and the posttest was 80% (BSB). From these results, it can be concluded that the smart roulette learning media is feasible to use to improve the social emotional aspects of children aged 5-6 years.